The complete mitochondrial genome of the Madagascar ground gecko Paroedura picta (Squamata: Gekkonidae) - Starostová, Zuzana; Musilová, Zuzana (Mitochondrial DNA. Part A, DNA mapping, sequencing, and analysis, 2016)
We sequenced the complete mitochondrial genome of the Madagascar ground gecko Paroedura picta (Squamata: Gekkonidae). The mitogenome is 17 220 base pairs long and conforms to the typical vertebrate gene composition and arrangement, i.e. 13 protein-coding genes, 22 tRNA genes, 2 ribosomal RNA genes and 1919 bp long control region. We reconstructed phylogenetic relationships of P. picta and representatives of nine other genera from the family Gekkonidae and calculated mean p-distances for all 13 protein-coding mitochondrial genes. The lowest mean p-distances were found in cytochrome oxidase subunit I and III genes (COI and COIII) indicating their usefulness for elucidating deeper phylogenetic relationships.
Keywords: Lizards; Sequence Analysis, DNA; biologická evoluce; mitochondrie; zastoupení bazí; long-range PCR; ještěři; Biological Evolution; DNA, Mitochondrial; mitogenome; genom mitochondriální; Genome; Gekkonidae; Gene Order; Base Sequence; sekvence nukleotidů; Madagascar; zvířata; Genes, Mitochondrial; Base Composition; mitochondriální DNA; fylogeneze; mtDNA; pořadí genů; genom; mitochondriální geny; sekvenční analýza DNA; Mitochondria; 454 pyrosequencing; lizard; Genome, Mitochondrial; Phylogeny; Madagaskar; Animals